PERSEPSI KONSUMEN TENTANG KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN LAYANAN INTERNET PROVIDER FIRST MEDIA AREA DEPOK - Muhamad Rizkie Agung Wiguna; Adelina Suryati (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This study aims to determine consumer perceptions of service quality and price on consumer satisfaction of First Media Area Depok Internet Service Provider. The method used in this study is a survey with a Quantitative approach. This study uses primary data and secondary data as data sources. Data were obtained by distributing questionnaires to 60 respondents. This analysis includes Validity Test and Reliability Test and hypothesis testing through t-Test and F-Test using SPSS Version 29.0. The results of this study indicate that the service quality variable has an influence and is significant to consumer satisfaction with a t-test p-Value of 0.001. while the price variable has no influence on consumer satisfaction with a t-test p-value of 0.152. From both variables, service quality and price simultaneously have an influence and are significant to consumer satisfaction with an F test of 0.001. Therefore.These two factors are very important for companies in an effort to attract consumers of the First Media Area Depok Internet Service Provider, it is advisable to continue to improve service quality and design effective pricing strategies to increase consumer satisfaction